Positive electrode material, secondary battery, and electric device

CN123017938APending Publication Date: 2026-10-30SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611301651.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]然而,锰基正极材料的商业化应用深受循环性能,特别是在高倍率下的容量衰减问题制约

Benefits of technology

本申请所提供的锰基正极材料基于第一元素在晶格中产生了显著的构型熵,从而在原子尺度构筑了一个稳固的多元网络,极大地束缚了锰离子的迁移,从而抑制了Jahn-Teller畸变与锰溶出等本征退化。这种高熵稳核机制与高度规整的尖晶石晶体结构相结合,使得该正极材料具备良好的结构完整性与优异的电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a positive electrode material, a secondary battery and an electric device. A first aspect of the application provides a positive electrode material, which comprises Li, Mn, O and a first element, the first element comprising at least one element selected from Al, Mg, Ni, Zr, Ti, Zn, Cu or Fe, the configurational entropy of the positive electrode material is greater than or equal to 1.5R, R is a gas constant, and the half-height width of the diffraction peak of the (111) crystal face in the X-ray diffraction spectrum of the positive electrode material is 0.08°-0.15°. The manganese-based positive electrode material provided by the application generates significant configurational entropy in the crystal lattice based on the first element, and constructs a stable multi-element network at the atomic scale, thereby binding the migration of manganese ions, and thereby inhibiting Jahn-Teller distortion and manganese dissolution. The high-entropy stable core mechanism is combined with the highly regular spinel crystal structure, so that the positive electrode material has good structural integrity and excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium battery technology, and in particular to cathode materials, secondary batteries and electrical equipment. Background Technology

[0002] The lithium-ion battery and cathode material industry has entered a stage of development characterized by large-scale, diversified, and high-end production. As the core carrier for lithium insertion / extraction, the cathode material directly determines the battery's energy density, power characteristics, cycle life, safety, and cost. Based on the different elements they contain, lithium-ion battery cathode materials can be classified into various types, including nickel-based, cobalt-based, phosphorus-based, and manganese-based cathode materials. Among these, manganese-based cathode materials are important due to their low cost, good safety, and environmental friendliness.

[0003] However, the commercial application of manganese-based cathode materials is severely limited by cycle performance, particularly capacity decay at high rates. This problem stems from intrinsic structural degradation during charge-discharge processes, including Jahn-Teller distortion, manganese ion dissolution, and irreversible phase transitions. When the battery reaches the end of its service life, the crystal structure of the cathode material is already damaged to varying degrees, making these problems even more pronounced. Therefore, there is an urgent need to develop a new manganese-based cathode material to overcome the bottlenecks of crystal structure stability and Jahn-Teller distortion in traditional manganese-based materials, thereby obtaining a cathode material with excellent overall electrochemical performance. Summary of the Invention

[0004] The main objective of this application is to provide a positive electrode material, a secondary battery, and an electrical device.

[0005] To achieve the above objectives, the first aspect of this application proposes a cathode material comprising Li, Mn, O and a first element, wherein the first element comprises at least one element selected from Al, Mg, Ni, Zr, Ti, Zn, Cu or Fe, and the configuration entropy ΔSconf of the cathode material is ≥1.5R, where R is a gas constant. In the X-ray diffraction pattern of the cathode material, the full width at half maximum (FWHM) of the diffraction peak of the (111) crystal plane is 0.08°~0.15°.

[0006] Configurational entropy is a thermodynamic physical quantity that describes the degree of disorder in the spatial arrangement of atoms or molecules within a system. When the configurational entropy ΔSconf ≥ 1.5R of the material in this application, the material can produce a significant high-entropy effect, including lattice distortion caused by the random occupancy of multi-element atoms and the hysteresis diffusion effect brought about by the multi-element chemical environment. Among these effects, the local stress field generated by the lattice distortion can effectively increase the energy barrier for manganese ions to escape from the lattice and inhibit their dissolution and migration into the electrolyte. The thermodynamic stability and hysteresis diffusion effect conferred by the high configurational entropy significantly enhance the material's ability to resist irreversible phase transitions.

[0007] The full width at half maximum (FWHM) can be any value among 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, and 0.15 degrees, or any value between any two adjacent values. If the FWHM of the diffraction peaks on the (111) crystal plane of the cathode material is within the above range, it indicates that at least a portion of the first element of the cathode material has been effectively doped into the crystal lattice and formed a uniform solid solution. This also indicates that the material has excellent crystal integrity, preventing excessive lattice defects from becoming preferential channels for manganese ion dissolution. Therefore, by adopting the technical solution of this embodiment, the cathode material can improve its resistance to irreversible phase transitions while suppressing the dissolution of manganese ions, thereby improving the cycle performance of the battery.

[0008] In some embodiments, the first element includes at least two elements selected from Al, Mg, Ni, Zr, Ti, Zn, Cu, or Fe. In some embodiments, the first element includes Al, and at least one of Mg, Ni, Zr, Ti, Zn, Cu, or Fe; in some embodiments, the first element includes Al and Mg.

[0009] In some embodiments, the first element includes at least three elements selected from Al, Mg, Ni, Zr, Ti, Zn, Cu, or Fe. In some embodiments, the first element includes Al and at least two elements selected from Mg, Ni, Zr, Ti, Zn, Cu, or Fe; in some embodiments, the first element includes Al, Mg, and at least one element selected from Ni, Zr, Ti, Zn, Cu, or Fe.

[0010] In some embodiments, the first element includes at least four elements selected from Al, Mg, Ni, Zr, Ti, Zn, Cu, or Fe. For example, the first element may include Al and at least three elements selected from Mg, Ni, Zr, Ti, Zn, Cu, or Fe. As another example, the first element may include Al, Mg, and at least two elements selected from Ni, Zr, Ti, Zn, Cu, or Fe. Yet another example, the first element may include Mg and at least three elements selected from Al, Ni, Zr, Ti, Zn, Cu, or Fe.

[0011] In some embodiments, the average relative deviation of the molar content of the same first element in the cathode material particles is less than 10%. This indicates that the first element has high uniformity of distribution in the cathode material particles, resulting in a solid solution distribution of the first element in the cathode material. In some embodiments, the average relative deviation of the molar content of the same first element in the cathode material particles is less than 5%.

[0012] The term "solid solution distribution" refers to the uniform dissolution of the primary element at the atomic scale within the lattice of the cathode material, resulting in a single, homogeneous solid phase without significant elemental segregation or a second phase. The uniformity of the solid solution distribution is characterized by arbitrarily selecting at least 10 microregions within a single particle, each 50 nm × 50 nm in size. STEM-EDS is used to measure the content of each primary element in each microregion, and the average relative deviation of the molar content of the same primary element between different microregions is calculated. When the average relative deviation of the same primary element between microregions does not exceed 10%, preferably not exceeding 5%, it indicates that the primary element has achieved a uniform solid solution distribution at the atomic scale, without elemental segregation or the formation of a second phase. The atomic-level solid solution distribution of the primary element is the structural basis for achieving the high-entropy effect. Only when the doped primary element is uniformly dispersed at the atomic scale within the lattice of the cathode material, rather than being enriched on the surface or forming an independent phase, can the synergistic stabilizing effect of multiple elements be fully utilized, thereby suppressing manganese ion migration and irreversible phase transitions.

[0013] In some embodiments, the cathode material is a manganese-based spinel oxide, and the chemical formula of the cathode material is Li. a Mn 2-x M x O4, 0.9≤a≤1.1, 0.04≤X<2, M is the first element. In some embodiments, X is any value from 0.04, 0.05, 0.06, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or any value between any two adjacent values. In some embodiments, a is any value from 0.9, 0.92, 0.94, 0.95, 0.96, 0.98, 1.00, 1.02, 1.04, 1.05, 1.06, 1.08, 1.1, or any value between any two adjacent values.

[0014] In one embodiment, the molar content of the first element in the cathode material satisfies: 0.8 ≤ X < 1.8. This can further optimize the stability of the cathode material. In another embodiment, the molar content of the first element in the cathode material satisfies: 1 ≤ X < 1.6.

[0015] In some implementations, the first element comprises a group consisting of Al, Mg, Ni, and Zr. These four elements are complementary in terms of ionic radius, valence, and chemical properties: Al 3+ and Mg 2+ As a robust structural stabilizer, Ni 2+ / 3+ It can effectively reduce Mn that causes Jahn-Teller distortion. 3+ Ratio, Zr 4+ It then acts as a high-charge "pinning agent" to further stabilize the crystal lattice.

[0016] In some implementations, the cathode material satisfies 0.5 ≤ (M Al +M Mg ) / M zr ≤2.0, M Al M represents the mole fraction of Al in the first element. Mg M represents the mole fraction of Mg in the first element. zr This represents the mole fraction of Zr in the first element.

[0017] In some embodiments, the intensity ratio I(400) / I(311) of the diffraction peaks of the (400) crystal plane and the (311) crystal plane of the cathode material is 1.2 to 2. I(400) / I(311) can be any value among 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, and 2, or any value between any two adjacent values. The lower limit (1.20) reflects the significant change in atomic site order after high-entropy doping, indicating that the multi-element has been successfully dissolved and a high-entropy effect has been generated, while the upper limit (2.00) avoids the risk of deviating from the pure spinel phase due to excessive lattice distortion.

[0018] In some embodiments, the particle size Dv50 of the cathode material is 200 nm to 2 μm. Dv50 can be any value from 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, and 2 μm, or any value between any two adjacent values. Here, Dv50 represents the particle size corresponding to a cumulative volume distribution ratio of 50% in the particles. When the particle size Dv50 of the cathode material is within the above range, interfacial side reactions of the cathode material can be reduced, and the lithium-ion solid-phase diffusion path can be shortened, which is beneficial to improving the rate performance of the secondary battery.

[0019] In some embodiments, the particle size distribution of the cathode material satisfies (Dv90-Dv10) / Dv50 ≤ 1.0. (Dv90-Dv10) / Dv50 can be any value among 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, 0.05, and 0.02, or any value between any two adjacent values. Here, Dv10, Dv50, and Dv90 represent the particle size corresponding to a cumulative volume distribution percentage of 10%, 50%, and 90% in the system, respectively. A particle size distribution span of (Dv90-Dv10) / D50 ≤ 1.0 ensures a narrow particle size distribution, which is beneficial for the consistency of electrode coating and the improvement of compaction density, thereby ensuring the uniformity of electrochemical performance. This uniform submicron particle size ensures an efficient lithium-ion transport path. The resulting high-entropy stable nucleus-homogeneous transport mechanism, combined with the highly ordered spinel crystal structure, enables manganese-based cathode materials to possess superior structural integrity and excellent long-cycle stability compared to traditional lithium manganese oxide materials, resulting in superior overall electrochemical performance.

[0020] In some embodiments, the oil absorption value of the cathode material is 15~35 mL / 100 g, for example, it can be any value among 15 mL / 100 g, 20 mL / 100 g, 25 mL / 100 g, 30 mL / 100 g, 35 mL / 100 g, etc., or any value between any two adjacent values. The oil absorption value of the cathode material indirectly reflects the primary particle aggregation state, affecting the pore distribution and electrolyte wetting channels after rolling. When the oil absorption value of the cathode material is within the above range, it is beneficial to the penetration of electrolyte and improve the rate performance of the battery.

[0021] In some embodiments, the aspect ratio of the cathode material is 1.0 to 1.5, for example, it can be any value among 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, or any value between any two adjacent values. When the aspect ratio of the cathode material is within the above range, the lithium-ion insertion / extraction channel can be optimized, and the lithium-ion insertion / extraction rate can be improved.

[0022] This application also relates to a method for preparing a cathode material, the method comprising the following steps: Manganese-based materials, lithium-supplementing materials, and materials corresponding to the first element are mixed and ground to obtain precursor composite powder; The precursor composite powder is sintered to obtain the cathode material.

[0023] In some embodiments, the manganese-based material can be lithium manganese oxide, which can be either decommissioned or non-decommissioned lithium manganese oxide. Using decommissioned lithium manganese oxide can reduce production costs. Decommissioned lithium manganese oxide is obtained by recycling the cathode material from decommissioned lithium manganese oxide batteries. In some embodiments, the decommissioned lithium manganese oxide battery is one whose capacity retention rate is less than 80%, failing to meet the original operating conditions.

[0024] In some embodiments, recycling the positive electrode material from retired lithium manganese oxide batteries includes: disassembling the retired lithium manganese oxide battery, separating the positive electrode sheet, and then separating the positive electrode active material layer of the positive electrode sheet to obtain retired lithium manganese oxide material. In some embodiments, a discharge step is included before disassembly. In some embodiments, the binder of the positive electrode sheet is removed before separating the positive electrode active material layer. In some embodiments, after separating the positive electrode active material layer, the material is crushed and screened to obtain retired lithium manganese oxide material powder. In some embodiments, the retired lithium manganese oxide material powder is analyzed for elemental composition before mixing. In some embodiments, the retired lithium manganese oxide material powder is pretreated before mixing. In some embodiments, the pretreatment includes acid washing, washing, and drying steps.

[0025] In some embodiments, the lithium supplementation material includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium acetate.

[0026] In some embodiments, the material corresponding to the first element includes at least one of the oxides or hydroxides of the first element.

[0027] In some implementations, the grinding method includes ball milling.

[0028] In some implementations, sintering is carried out using a stepped heating sintering method.

[0029] In some embodiments, the sintering temperature is 600 ℃ to 1200 ℃, for example, it can be any value among 600 ℃, 650 ℃, 700 ℃, 750 ℃, 800 ℃, 850 ℃, 900 ℃, 950 ℃, 1000 ℃, 1050 ℃, 1100 ℃, 1150 ℃ or 1200 ℃, or any value between any two adjacent values. In some embodiments, the heating rate is 1 to 20 °C / min, for example, it can be any value among 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min, 10 °C / min, 11 °C / min, 12 °C / min, 13 °C / min, 14 °C / min, 15 °C / min, 16 °C / min, 17 °C / min, 18 °C / min, 19 °C / min or 20 °C / min, or any value between any two adjacent values.

[0030] In some embodiments, the sintered product also includes a grinding and sieving step.

[0031] A second aspect of this application provides a secondary battery, including a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode includes the positive electrode material of the first aspect of this application.

[0032] In some embodiments, the electrolyte includes any one of a solid electrolyte, a gel electrolyte, or a liquid electrolyte (i.e., a liquid electrolyte solution).

[0033] In some embodiments, the electrolyte includes an electrolyte salt and an organic solvent. In some embodiments, the organic solvent includes at least one selected from ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate. In some embodiments, the electrolyte also includes additives, such as film-forming additives (e.g., vinylene carbonate, 1,3-propanesulfonate lactone) and at least one selected from low-temperature additives and flame-retardant additives (e.g., phosphate esters). In some embodiments, the electrolyte salt includes an electrolyte lithium salt, such as at least one selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium di(oxalateborate)borate (LiBOB), or lithium di(fluorooxalateborate)borate (LiODFB).

[0034] In some embodiments, the positive and negative electrode sheets in the secondary battery are obtained by at least one method such as stacking or winding to form a cell, thereby producing the secondary battery.

[0035] In some embodiments, the positive electrode includes a positive current collector layer and a positive active material layer.

[0036] In some implementations, the positive current collector layer comprises aluminum material, such as aluminum foil.

[0037] In some embodiments, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material includes the doped lithium manganese oxide positive electrode material described in the first aspect. In some embodiments, the positive electrode active material layer further includes at least one of a conductive agent, a binder, or a thickener. In some embodiments, the conductive agent includes at least one of conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT), or graphene. In some embodiments, the binder includes at least one of polyisobutylene (PIB), styrene-butadiene rubber (SBR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), hydrogenated styrene-butadiene block copolymer (SEBS), ethyl cellulose (EC), polyurethane (PU), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), and polyvinyl butyral (PVB). In some embodiments, the thickener includes at least one of carboxymethyl cellulose (CMC), hydroxypropyl methyl cellulose (HPMC), or hydroxyethyl cellulose (HEC).

[0038] In some embodiments, the compaction density of the positive electrode is 2.4~2.8 g / cm³. 3 For example, it could be 2.4 g / cm³. 3 2.45 g / cm 3 2.5 g / cm 3 2.55 g / cm 3 2.6 g / cm 3 2.65 g / cm 3 2.7 g / cm 3 2.75 g / cm 3 2.8g / cm 3 Any value in the range, or any value between any two adjacent values. Compaction density within the above range is beneficial for improving the energy density of the battery.

[0039] In some embodiments, the porosity of the positive electrode is 25-35%, for example, it can be any value among 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, and 35%, or any value between any two adjacent values. A porosity within the above range can improve the lithium-ion insertion / extraction rate and enhance the rate performance of the battery.

[0040] In some embodiments, the negative electrode sheet includes a negative electrode current collector layer and a negative electrode active material layer.

[0041] In some embodiments, the negative electrode current collector layer comprises copper, such as copper foil. Alternatively, the negative electrode current collector layer may also be nickel (e.g., nickel foil), steel (e.g., stainless steel foil), or a polymer composite current collector with a copper-coated surface. The aforementioned metal current collector layer may be manufactured by electrolysis, rolling, or other processes well known in the art.

[0042] In some embodiments, the negative electrode active material layer includes the positive electrode active material. In some embodiments, the negative electrode active material includes at least one of carbon-based materials, silicon-based materials, or carbon-silicon composite materials. In some embodiments, the carbon-based material includes at least one of natural graphite, artificial graphite, hard carbon, soft carbon, and mesophase carbon microspheres. In some embodiments, the negative electrode active material layer further includes at least one of a conductive agent, a binder, or a thickener. In some embodiments, the conductive agent includes at least one of conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT), or graphene. In some embodiments, the binder includes at least one of polyisobutylene (PIB), styrene-butadiene rubber (SBR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), hydrogenated styrene-butadiene block copolymer (SEBS), ethyl cellulose (EC), polyurethane (PU), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), or polyvinyl butyral (PVB). In some embodiments, the thickener includes at least one of sodium carboxymethyl cellulose (CMC-Na), hydroxypropyl methylcellulose (HPMC), or hydroxyethyl cellulose (HEC).

[0043] In some embodiments, the secondary battery further includes a separator. In some embodiments, the separator material includes at least one selected from polyolefins (such as polyethylene, polypropylene), polyacrylonitrile, polyvinylidene fluoride, polyimide, polybenzimidazole, polyethylene terephthalate, polybutylene terephthalate, polyamide, polyacetal, polycarbonate, polyetherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, polyethylene naphthalate, polytetrafluoroethylene, polyvinyl chloride, poly(p-phenylenebenzodiazole), or polyarylates. In some embodiments, the separator is a single-layer or multi-layer separator. In some embodiments, the separator also has a surface-modified coating, such as a composite separator with a ceramic coating like alumina or silica, or a polymer coating like polyvinylidene fluoride or aramid polymers. Furthermore, it also includes separators with special substrates, such as nonwoven fabrics, electrospun fiber membranes, or gel polymer membranes.

[0044] A third aspect of this application provides an electrical device including the secondary battery described in the second aspect of this application.

[0045] In some implementations, the electrical equipment includes mobile phones, smartphones, laptops, tablets, wearable devices, smartwatches, smart bracelets, smart glasses, power banks, televisions, game consoles, game controllers, digital cameras, smart speakers, headphones, keyboards, mice, monitors, drones, audio equipment, home appliances, toys, power tools, automobiles, motorcycles, electric bicycles, bicycles, robots, robot dogs, industrial robots, android robots, etc.

[0046] The beneficial effects of this application are: The manganese-based cathode material provided in this application generates significant configurational entropy in the crystal lattice due to the presence of the first element, thereby constructing a robust multi-element network at the atomic scale. This significantly restricts the migration of manganese ions, thus suppressing intrinsic degradation such as Jahn-Teller distortion and manganese dissolution. This high-entropy nucleation mechanism, combined with the highly ordered spinel crystal structure, gives the cathode material excellent structural integrity and superior electrochemical performance. Detailed Implementation

[0047] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. The terminology used herein is for the purpose of describing embodiments of this application only and is not intended to limit the application. Those skilled in the art will recognize that, with the evolution of technology and the emergence of new application scenarios, the technical solutions provided in the embodiments of this application are equally applicable to similar technical problems.

[0048] Example 1 This embodiment provides a cathode material with the following general formula: LiMn 0.4 Al 0.4 Mg 0.4 Ni 0.4 Zr 0.4 O4. The specific preparation method of this cathode material is as follows: (1) Immerse the retired lithium manganese oxide power battery in a 5 wt.% sodium chloride aqueous solution for 48 hours until the open circuit voltage drops below 0.5 V.

[0049] (2) Disassemble the battery in an argon-protected glove box and separate the positive electrode. Cut the electrode into small pieces of 2 cm × 2 cm, place them in a tube furnace, and heat them to 450 ℃ at 5 ℃ / min under a nitrogen atmosphere. Hold the temperature for 2 hours to remove the polyvinylidene fluoride (PVDF) binder.

[0050] (3) After cooling, the electrode coating is peeled off from the aluminum foil, and after crushing and screening, retired lithium manganese oxide cathode material powder is obtained. A portion of the powder is subjected to inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis, and the molar ratio of the main elements is found to be Li:Mn=0.80:2.00, the Al content is 0.15 wt.%, and the content of other impurity elements is less than 0.1 wt.%.

[0051] (4) Weigh 100.0 g of the decommissioned lithium manganese oxide cathode material powder obtained in step (3) and place it in a 1 L polytetrafluoroethylene beaker. Add 300 mL of 0.2 mol / L dilute sulfuric acid solution and stir at 500 rpm for 30 minutes to remove residual lithium salts and soluble impurities from the surface. Then wash repeatedly with deionized water until neutral, filter, and vacuum dry at 80℃ for 12 hours to obtain pretreated active powder. The powder contains approximately 60.2 wt.% Mn.

[0052] (5) Based on the Mn of the pretreated active powder in step (4), accurately weigh 84.98 g of Li2CO3, 85.44 g of Al(OH)3, 44.16 g of MgO, 81.84 g of NiO, and 135.04 g of ZrO2, and put them into a ball mill jar. Add grinding balls and 600 mL of anhydrous ethanol as the dispersion medium, set the speed to 380 rpm, and ball mill for 10 hours.

[0053] (6) After ball milling, pour the slurry into a glass dish and dry it in a vacuum drying oven at 80 ℃ for 24 hours. Grind the dried material slightly and sieve it through a 100-mesh sieve to obtain the precursor composite powder.

[0054] (7) Spread the precursor powder evenly in the boat, place the boat in the constant temperature zone of the tube furnace, and seal the furnace body. Introduce air at a flow rate of 2 L / min to establish a stable air atmosphere, and then carry out stepwise heating sintering: first, heat to 650 ℃ at a heating rate of 10 ℃ / min and hold for 2 hours; then heat to 880 ℃ at a heating rate of 4 ℃ / min and hold at this temperature for 12 hours.

[0055] (8) After the heat preservation is completed, the furnace is naturally cooled to room temperature in a continuous air flow (1 L / min).

[0056] (9) Take out the sintered product, grind it gently in a mortar for 5 minutes, and then sieve it through a 400-mesh sieve to obtain the final positive electrode material.

[0057] This embodiment also provides a secondary battery, the preparation process of which is as follows: Positive electrode fabrication: The positive electrode material prepared above, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 94:3:3, and then thoroughly dispersed in N-methylpyrrolidone (NMP) solvent to form a uniform slurry. The slurry was coated onto both surfaces of a 15 μm aluminum foil. The electrode was then dried and rolled (compacted density 2.6 g / cm³). 3 The process involves slitting and die-cutting to obtain LMO cathode sheets (porosity 30%).

[0058] Negative electrode fabrication: Graphite, conductive carbon black, sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) are mixed in a mass ratio of 95:1.5:1.5:2.0. Deionized water solvent is added, and the mixture is stirred at high speed to form a homogeneous slurry. This slurry is coated onto a 4.5 μm copper foil, vacuum dried at 120℃, and then rolled (compacted density 1.5 g / cm³). 3 The negative electrode sheet is obtained by cutting and splitting.

[0059] Separator: A composite separator consisting of a PP substrate and a ceramic coating is used.

[0060] Electrolyte: Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1:1 as a solvent. LiPF6 is added to prepare a 1.0 mol / L solution. Then, 2% by mass of vinylene carbonate (VC) and 3% by mass of fluoroethylene carbonate (FEC) additives are added and mixed evenly.

[0061] The positive and negative electrode sheets, separator, and electrolyte prepared above are processed into lithium manganese oxide batteries through processes such as winding, hot pressing, welding, baking, liquid injection, formation, capacity testing, and settling.

[0062] Example 2 This embodiment provides a cathode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the general formula of the cathode material is LiMn. 0.4 Al 0.4 Mg 0.4 Ni 0.4 Ti 0.4 O4 was prepared by replacing ZrO2 with an equimolar amount of TiO2. The resulting positive electrode sheet had a compaction density of 2.6 g / cm³. 3 The porosity is 30%.

[0063] Example 3 This embodiment provides a cathode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the general formula of the cathode material is LiMn. 0.8 Al 0.3 Mg 0.3 Ni 0.3 Zr0.3 O4 was prepared by adjusting the amounts of Al(OH)3, MgO, NiO, and ZrO2 according to the general formula. The resulting positive electrode sheet had a compaction density of 2.6 g / cm³. 3 The porosity is 30%.

[0064] Example 4 This embodiment provides a cathode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the general formula of the cathode material is LiMn. 0.4 Al 0.4 Cu 0.4 Zn 0.4 Fe 0.4 O4 is prepared by selecting the appropriate amounts of Al(OH)3, CuO, ZnO, and Fe2O3. The resulting positive electrode sheet has a compaction density of 2.6 g / cm³. 3 The porosity is 30%.

[0065] Example 5 This embodiment provides a positive electrode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the sintering temperature in the second stage of heating in step (7) of the positive electrode material preparation method is increased from 880 ℃ to 920 ℃. The rolling pressure during the positive electrode sheet preparation process is also adjusted, wherein the compacted density of the obtained positive electrode sheet is 2.4 g / cm³. 3 The porosity is 25%.

[0066] Example 6 This embodiment provides a positive electrode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the sintering temperature in the second stage of heating in step (7) of the positive electrode material preparation method is reduced from 880 ℃ to 840 ℃. The rolling pressure during the positive electrode sheet preparation process is also adjusted, wherein the compacted density of the obtained positive electrode sheet is 2.8 g / cm³. 3 The porosity is 35%.

[0067] Example 7 This embodiment provides a cathode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the general formula of the cathode material is LiMn. 0.2 Al 0.45 Mg 0.45 Ni 0.45 Zr 0.45 O4 was prepared by adjusting the amounts of Al(OH)3, MgO, NiO, and ZrO2 according to the general formula. The resulting positive electrode sheet had a compaction density of 2.6 g / cm³. 3 The porosity is 30%.

[0068] Example 8 This embodiment provides a cathode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the general formula of the cathode material is LiMn. 0.4 Mg 0.4 Ni 0.4 Zr 0.4 Ti 0.4 O4 was prepared by replacing Al(OH)3 with an equimolar amount of TiO2. The resulting positive electrode sheet had a compaction density of 2.6 g / cm³. 3 The porosity is 30%.

[0069] Example 9 This embodiment provides a cathode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the general formula of the cathode material is LiMn. 0.4 Al 0.32 Mg 0.32 Ni 0.32 Zr 0.32 Ti 0.32 O4 was prepared by adjusting the amounts of Al(OH)3, MgO, NiO, ZrO2, and TiO2 according to the general formula. The resulting positive electrode sheet had a compaction density of 2.6 g / cm³. 3 The porosity is 30%.

[0070] Example 10 This embodiment provides a cathode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the general formula of the cathode material is LiMn. 0.8 Al 0.2 Mg 0.2 Ni 0.2 Zr 0.2 Ti 0.2 Zn 0.2 O4 was prepared by adjusting the amounts of Al(OH)3, MgO, NiO, ZrO2, TiO2, and ZnO according to the general formula. The resulting positive electrode sheet had a compaction density of 2.6 g / cm³. 3 The porosity is 30%.

[0071] Example 11 This embodiment provides a cathode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the general formula of the cathode material is LiMn. 0.6 Al 0.2 Mg 0.2 Ni 0.2 Zr 0.2 Ti 0.2 Zn 0.2 Cu 0.2O4 was prepared by adjusting the amounts of Al(OH)3, MgO, NiO, ZrO2, TiO2, ZnO, and CuO according to the general formula. The resulting positive electrode sheet had a compaction density of 2.6 g / cm³. 3 The porosity is 30%.

[0072] Example 12 This embodiment provides a cathode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the general formula of the cathode material is LiMn. 0.4 Al 0.2 Mg 0.2 Ni 0.2 Zr 0.2 Ti 0.2 Zn 0.2 Cu 0.2 Fe 0.2 O4 was prepared by adjusting the amounts of Al(OH)3, MgO, NiO, ZrO2, TiO2, ZnO, CuO, and Fe2O3 according to the general formula. The resulting positive electrode sheet had a compaction density of 2.6 g / cm³. 3 The porosity is 30%.

[0073] Examples 13-15 This embodiment provides a cathode material and a corresponding secondary battery. The only difference from Embodiment 1 is that the temperature of the stepped heating sintering is adjusted to obtain cathode materials with different aspect ratios and oil absorption values.

[0074] Comparative Example 1 This comparative example provides a cathode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the cathode material preparation method, only Li2CO3 is used for lithium supplementation, and the general formula of the resulting cathode material is Li. 1.05 Mn 1.95 O4. The compaction density of the resulting positive electrode sheet is 2.6 g / cm³. 3 The porosity is 30%.

[0075] Comparative Example 2 This comparative example provides a cathode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the cathode material preparation method, Li2CO3 and a small amount of Al(OH)3 are added for lithium replenishment and doping, and the general formula of the cathode material obtained is LiMn. 1.9 Al 0.1 O4. The compaction density of the resulting positive electrode sheet is 2.6 g / cm³. 3 The porosity is 30%.

[0076] Comparative Example 3 This comparative example provides a cathode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the cathode material preparation method, Li2CO3 and an appropriate amount of Al(OH)3 are added for lithium supplementation and doping, and the general formula of the cathode material obtained is LiMn. 1.5 Al 0.5 O4. The compaction density of the resulting positive electrode sheet is 2.6 g / cm³. 3 The porosity is 30%.

[0077] Comparative Example 4 This comparative example provides a cathode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the cathode material preparation method, Li2CO3 and appropriate amounts of Al(OH)3, MgO, NiO, and ZrO2 are added for lithium supplementation and doping. The general formula of the cathode material obtained is LiAl. 0.5 Mg 0.5 Ni 0.5 Zr 0.5 O4 was introduced in excess of the first element during the formulation process, causing Mn to be completely substituted in the main phase. After high-temperature sintering, Mn formed an independent oxide impurity phase and was removed, resulting in a cathode material without manganese. Although this material can form a spinel structure, it no longer exhibits lithium manganese oxide activity. The compaction density of the prepared cathode sheet was 2.6 g / cm³. 3 The porosity is 30%.

[0078] Comparative Example 5 This comparative example provides a positive electrode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the positive electrode material preparation method, after weighing the required amounts of each raw material, they are simply mixed without ball milling. The compacted density of the obtained positive electrode sheet is 2.6 g / cm³. 3 The porosity is 30%.

[0079] Comparative Example 6 This comparative example provides a cathode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the cathode material preparation method, Li2CO3 and appropriate amounts of Al(OH)3 and MgO are added for lithium supplementation and doping, and the general formula of the cathode material obtained is LiMn. 1.2 Al 0.45 Mg 0.35 O4. The compaction density of the resulting positive electrode sheet is 2.6 g / cm³. 3 The porosity is 30%.

[0080] Comparative Example 7 This comparative example provides a cathode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the cathode material preparation method, Li2CO3 and appropriate amounts of Al(OH)3, MgO, and NiO are added for lithium supplementation and doping. The general formula of the cathode material obtained is LiMn. 0.95 Al 0.35 Mg 0.35 Ni 0.35 O4. The compaction density of the resulting positive electrode sheet is 2.6 g / cm³. 3 The porosity is 30%.

[0081] Comparative Example 8 This comparative example provides a cathode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the cathode material preparation method, Li2CO3 and an appropriate amount of Co3O4 are added for lithium supplementation and doping, and the general formula of the cathode material obtained is LiMn. 1.92 Co 0.08 O4. The compaction density of the resulting positive electrode sheet is 2.6 g / cm³. 3 The porosity is 30%.

[0082] Comparative Example 9 This comparative example provides a cathode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the cathode material preparation method, Li2CO3 and appropriate amounts of Al(OH)3, MgO, and La2O3 are added for lithium supplementation and doping. The general formula of the cathode material obtained is LiMn. 0.8 Al 0.4 Mg 0.4 La 0.4 O4. The compaction density of the resulting positive electrode sheet is 2.6 g / cm³. 3 The porosity is 30%.

[0083] Comparative Example 10 This comparative example provides a cathode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the cathode material preparation method, Li2CO3 and appropriate amounts of Al(OH)3, MgO, NiO, and La2O3 are added for lithium supplementation and doping. The general formula of the cathode material obtained is LiMn. 0.4 Al 0.4 Mg 0.4 Ni 0.4 La 0.4 O4. The compaction density of the resulting positive electrode sheet is 2.6 g / cm³. 3 The porosity is 30%.

[0084] Comparative Example 11 This comparative example provides a positive electrode material and a corresponding secondary battery. The only difference from Example 1 is that in step (5) of the positive electrode material preparation method, the amounts of Al(OH)3, MgO, NiO, and La2O3 are adjusted, and the general formula of the final positive electrode material is LiMn. 0.8 Al 0.6 Mg 0.2 Ni 0.2 La 0.2 O4. The compaction density of the resulting positive electrode sheet is 2.6 g / cm³. 3 The porosity is 30%.

[0085] The cathode materials obtained in the above embodiments and comparative examples were tested using the following specific testing methods: 1. Method for determining particle size and particle size distribution: The particle size and distribution of the cathode material were determined using a laser particle size analyzer. The powder sample was ultrasonically dispersed in deionized water and then dropped into the sample cell. The material refractive index was set to 2.20 and the absorptivity to 0.10. The test was conducted under stirring and circulation conditions, with the opacity controlled between 8% and 12%. The instrument software statistically output the values ​​of Dv10, Dv50, and Dv90 according to the volume distribution. Dv10, Dv50, and Dv90 represent the particle size corresponding to a cumulative volume distribution percentage of 10%, 50%, and 90% in the system, respectively.

[0086] 2. X-ray diffraction (XRD) and full width at half maximum (FWHM) determination method: The FWHM of the (111) crystal plane diffraction peak was determined by powder X-ray diffraction. Using Cu Kα rays as the radiation source, the (111) diffraction peak near 2θ=18.5° was finely scanned at a scanning rate of 1° / min and a step size of 0.01° to obtain the fine XRD scan pattern. After the Kα2 peak was stripped, the (111) diffraction peak was fitted with the Pseudo-Voigt function, and the FWHM of the fitted peak was recorded as the sample's FWHM.

[0087] 3. Method for determining the diffraction peak intensity ratio I(400) / I(311): Based on the above fine XRD scanning pattern, after subtracting the background, the (400) diffraction peak near 2θ=44° and the (311) diffraction peak near 2θ=36.5° were integrated to obtain their respective integrated areas. Using the (311) peak area as the normalization benchmark, the ratio was calculated according to the formula I(400) / I(311)=integrated area(400) / integrated area(311).

[0088] 4. Method for determining and calculating configuration entropy (ΔSconf): First, the contents of Li, Mn, and each dopant element in the sample were determined using ICP-OES and converted into the mole fraction of each metal relative to the total cations. Second, Rietveld refinement (space group Fd-3m) was performed using XRD patterns to determine the occupancy rate and mole fraction ci of each metal at the 16d site. The configuration entropy was calculated using the following formula: ΔSconf = -RΣ(ci lnci), where R is the gas constant (8.314 J·mol⁻¹). -1 ·K -1 The summation is limited to Mn and dopants at the 16d site, excluding Li occupying the 8a site. The results are expressed as multiples of R.

[0089] 5. Method for determining the oil absorption value of positive electrode materials: Weigh approximately 1 g of the powder to be tested and place it on a clean glass plate. Use dibutyl phthalate (DBP) as the titration medium and continuously mix it with a spatula during the titration process. The titration endpoint is reached when the powder just forms a uniform paste-like mass, and there is no loose powder falling off the surface of the mass and no free liquid residue on the glass plate. The oil absorption value is expressed as the number of milliliters of DBP consumed per 100 g of sample, and is calculated using the following formula: Oil absorption value OA (mL / 100g) = (V×100) / m, where V is the volume of DBP consumed (mL) and m is the sample mass (g).

[0090] 6. Method for determining the aspect ratio of the cathode material: Take an appropriate amount of powder sample, ultrasonically disperse it in anhydrous ethanol, drop it onto a silicon wafer or conductive tape, dry it, and then observe it on an SEM sample stage. At a magnification of [insert magnification here], randomly select no fewer than 10 fields of view, ensuring that the particle outlines are clear and isolated in each field of view. Randomly measure no fewer than 100 particles, and for each particle, measure its longest axis length L and the shortest axis length S perpendicular to the longest axis. The aspect ratio is calculated using the following formula: Aspect ratio λ = L / S.

[0091] The results are shown in Table 1.

[0092] Table 1. Detection results of cathode material parameters

[0093] The performance of the secondary batteries obtained in the above embodiments and comparative examples was tested. The specific test items, test methods, and results are as follows: 1) 1 C rate cycle performance test: At 25±2 ℃, the secondary battery is charged and discharged at a rate of 1 C / 1 C within the range of 3.0~4.3 V. The discharge specific capacity of the battery in the first cycle and the discharge specific capacity after 1000 cycles are recorded. The capacity retention rate after 1000 cycles = discharge specific capacity after 1000 cycles / discharge specific capacity in the first cycle × 100%.

[0094] 2) 5C capacity retention test: At 25±2 ℃, the secondary battery was first charged to 4.3 V at a constant current and constant voltage of 0.33 C, and then discharged to 3.0 V at constant current rates of 0.33 C, 0.5 C, 1 C, 2 C and 5 C respectively. The discharge specific capacity at each rate was recorded; 5C rate discharge capacity retention rate = 5C discharge specific capacity / 0.33 C discharge specific capacity × 100%.

[0095] 3) First-cycle coulombic efficiency test: At room temperature, the battery under test was charged to 4.3V at a constant current of 0.33 C, and then charged at a constant voltage of 4.3V until the current dropped to 0.05 C. After standing for 30 min, it was discharged to 3V at a constant current of 0.33 C. The first discharge capacity C1 and the first charge capacity C0 were recorded. The first-cycle coulombic efficiency = (C1 / C0) × 100%.

[0096] Table 2. Performance Test Results of Secondary Batteries

[0097] Comparing Comparative Examples 1-10, compared to the traditional lithium replenishment regeneration method in Comparative Example 1, the electrochemical performance of Comparative Examples 2, 3, and 8 was improved by using different amounts of single-element doping. While Comparative Examples 6 and 7, using two or three elements, also showed some improvement in electrochemical performance, the effect of two elements in Comparative Example 6 was insufficient to surpass the single-element doping effect of Comparative Example 2. This indicates that there is no direct positive correlation between the type of doping element and the doping effect. Although Comparative Examples 7 and 9 both used three elements, Comparative Example 9 included La, which is not within the scope of this application, resulting in a lower effect compared to Comparative Example 7. Similarly, Comparative Example 10, by replacing Zr with La compared to Example 1, showed a significant decrease in all aspects of performance. In Comparative Example 4, Mn was completely replaced, losing its original lithium manganese oxide activity. Therefore, although it also retained four doping elements within the scope, its electrochemical performance was even significantly lower than that of traditional lithium replenishment regeneration.

[0098] Comparing Example 1 and the Comparative Example, it can be seen that Example 1 uses specific doping elements to dope the regenerated lithium manganese oxide material, and its configuration entropy and the full width at half maximum (FWHM) of the diffraction peak of the (111) crystal plane are within the expected range. Ultimately, Example 1 shows a significant improvement in various aspects of electrochemical performance, including cycle performance and rate performance. This is something that cannot be achieved by using traditional lithium replenishment regeneration, or by failing to adjust the configuration entropy and FWHM to the predetermined range, or by using other elements within the range for doping. Comparative Example 5 did not use ball milling, and the simple stirring it used could only achieve micron-level mixing, resulting in insufficient mixing between the various elements. Consequently, it could not form an atomic-level solid solution distribution during sintering. Therefore, although it used four specific elements, its performance was still far behind that of Example 1, which used high-energy ball milling to break the precursor to the nanoscale and generate lattice defects, significantly shortening the diffusion path. In addition, although Comparative Example 11 also used four specific elements, the amounts of these elements differed greatly, and the ratio deviated significantly from equimolarity. The configuration entropy could not reach 1.5R, and the high-entropy effect could not be triggered. Although its performance is significantly enhanced compared to other comparative examples, there is still considerable room for improvement in performance compared to Example 1.

[0099] Comparing Examples 1, 2, 4, and 8, the element Ti was doped in Example 2. 4+ Replace Zr 4+ The high-charge "pinning" effect is due to Ti 4+ Smaller radius and weakened; Ti in the doped element in Example 8 4+ Replace Al 3+ Subsequently, the system lacked small-radius, low-valence framework supporting ions, resulting in an imbalance of functional roles; the electrochemical performance of both decreased. Example 4 replaced three doping elements, and the synergistic complementary relationship of the element combination in terms of ionic radius, valence state, and chemical properties deviated more significantly from the preferred range of the present invention. Therefore, the performance degradation was more obvious than that of Examples 2 and 8, which replaced only one element.

[0100] Comparing Examples 1, 5, and 6, the performance of the products varies depending on the sintering temperature. As the sintering temperature of the second stage increases, the electrochemical performance of the resulting cathode material first increases and then decreases.

[0101] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that, The cathode material includes Li, Mn, O and a first element, the first element including at least one of Al, Mg, Ni, Zr, Ti, Zn, Cu or Fe, the configuration entropy ΔSconf of the cathode material is ≥1.5R, where R is the gas constant, and in the X-ray diffraction pattern of the cathode material, the half-width at half-maximum (WHM) of the diffraction peak of the (111) crystal plane is 0.08°~0.15°.

2. The cathode material according to claim 1, characterized in that, The first element includes at least two elements selected from Al, Mg, Ni, Zr, Ti, Zn, Cu, or Fe.

3. The cathode material according to claim 1, characterized in that, The first element includes at least four elements selected from Al, Mg, Ni, Zr, Ti, Zn, Cu, or Fe.

4. The cathode material according to any one of claims 1 to 3, characterized in that, The cathode material is a manganese-based spinel oxide, and the chemical formula of the cathode material is Li. a Mn 2-x M x O4, 0.9≤a≤1.1, 0.04≤x<2, M is the first element.

5. The positive electrode material according to claim 4, characterized in that, The first element comprises a set consisting of Al, Mg, Ni, and Zr.

6. The positive electrode material according to claim 5, characterized in that, In the aforementioned cathode material, 0.5 ≤ (M) Al +M Mg ) / M Zr ≤2.0, M Al M represents the mole fraction of Al in the first element. Mg M represents the mole fraction of Mg in the first element. zr This represents the mole fraction of Zr in the first element.

7. The cathode material according to claim 1, characterized in that, The intensity ratio of the diffraction peaks of the (400) crystal plane to the (311) crystal plane of the cathode material is 1.2~2.

8. The positive electrode material according to claim 1, characterized in that, The particle size Dv50 of the cathode material is 200 nm to 2 μm, where Dv50 represents the particle size when the cumulative volume distribution of particles reaches 50%.

9. The positive electrode material according to claim 1, characterized in that, The particle size distribution of the cathode material satisfies (Dv90-Dv10) / Dv50≤1.0, where Dv10, Dv50 and Dv90 represent the particle sizes corresponding to the cumulative volume distribution of particles reaching 10%, 50% and 90%, respectively.

10. The cathode material according to claim 1, characterized in that, The oil absorption value of the positive electrode material is 15~35mL / 100g.

11. The cathode material according to claim 1, characterized in that, The aspect ratio of the positive electrode material is 1.0 to 1.

5.

12. A secondary battery, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises the positive electrode material according to any one of claims 1 to 11.

13. The secondary battery according to claim 12, characterized in that, The compaction density of the positive electrode sheet is 2.4~2.8 g / cm³. 3 And / or the porosity of the positive electrode is 25%~35%.

14. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 12 or 13.